LBD14/ASL17 Positively Regulates Lateral Root Formation and is Involved in ABA Response for Root Architecture in Arabidopsis. (11th October 2017) - Jeon, Eunkyeong; Young Kang, Na; Cho, Chuloh; Joon Seo, Pil; Chung Suh, Mi; Kim, Jungmook
Abstract: The LATERAL ORGAN BOUNDARIES ( LOB ) DOMAIN / ASYMMETRIC LEAVES2-LIKE ( LBD / ASL ) gene family members play key roles in diverse aspects of plant development. Previous studies have shown that LBD16, 18, 29 and 33 are critical for integrating the plant hormone auxin to control lateral root development in Arabidopsis thaliana. In the present study, we show that LBD14 is expressed exclusively in the root where it promotes lateral root (LR) emergence. Repression of LBD14 expression by ABA correlates with the inhibitory effects of ABA on LR emergence. Transient gene expression assays with Arabidopsis protoplasts demonstrated that LBD14 is a nuclear-localized transcriptional activator. The knock-down of LBD14 expression by RNA interference (RNAi) resulted in reduced LR formation by delaying both LR primordium development and LR emergence, whereas overexpression of LBD14 in Arabidopsis enhances LR formation. We show that ABA (but not other plant hormones such as auxin, brassinosteroids and cytokinin) specifically down-regulated β-glucuronidase (GUS) expression under the control of the LBD14 promoter in transgenic Arabidopsis during LR development from initiation to emergence and endogenous LBD14 transcript levels in the root. Moreover, RNAi of LBD14 enhanced the LR suppression in response to ABA, whereas LBD14 overexpression did not alter the ABA-mediated suppression of LR formation. Taken together, these results suggest that LBD14 promoting LR formation is one of the critical factors regulated by ABA to inhibit LR growth, contributing to the regulation of the Arabidopsis root system architecture in response to ABA.